The Effect Of Monopoly Talabasa To Improve Vocabulary At Sixth Grade Of SDN 1 Tanjung Gading - Nurul Khotimah; Harpain, Harpain; Izef Puspadani Damanik (International Journal of Education, Vocational and Social Science, 2024)
This research is to assess the extent to which Monopoly Talabasa can have a significant influence on enhancing students' English vocabulary. This study used a quantitative method with control and experimental classes. Each received treatment for four meetings. Pretest to know students' initial English vocabulary abilities before treatment. The studies population consisted of class VI students at SDN 1 Tanjung Gading. The instruments used for data collection used pretest and posttest. The results of data analysis showed a significant increase in students' vocabulary. The pretest score for the control class was 59.40 and the pretest score for the experimental class was 63.20. Meanwhile, the posttest score of the control class reached 73.60 and the experimental class reached 80.00, with an increase in control class was 14.20 and the experimental class was 16.80. Statistical analysis showsed a significant difference with a value of 0.022<0.050 indicating that the use of Monopoly Talabasa had a significant positive impact on increasing students' vocabulary. So, teaching using Monopoly Talabasa may be effective in increasing students' English vocabulary.